Sifat fisik dan mekanik balok lamina dari batang kelapa sawit berdasarkan jumlah lapisan [ The physical and mechanical properties of laminated lumber from oil palm trunk based on the number of layers] - Harsono, Dwi; Ihsan, Hamlan; Miyono, Miyono; Setiawati, Evy (Jurnal Riset Industri Hasil Hutan, 2021)
The total area of oil palm plantations in 2019 is 14.2 million hectares. Every 25 years, there is always oil palm plantations replanting that produced oil palm trunks. The potential of oil palm trunks used as raw material for laminated lumber is about 52.5% of the total of oil palm biomass. Oil palm trunks have a very low density, so that it needs special processing before it could be applied as building material or other uses. The purpose of this study is to analyze the physical and mechanical properties of laminated lumber from oil palm trunks at the end position based on the number of layers. The method used in this research was the utilization of oil palm trunks lamination using PVAc (polyvinyl acetate) adhesive with variations of 1, 2, 3, and 4 layers. The results showed that oil palm trunks could be used as raw material for laminated lumber. The characteristics of laminated lumber made from 1, 2, 3, and 4 layers range between: moisture content (12.16–13.6) %, density (1.281–0.331) g/cm3, MoR (65.46–116.54) kg/cm2, and compressive strength parallel to its fibers (43.31–114,66) kg/cm2. The physical properties of the oil palm trunks laminated lumber with the increasing number of layers tends to increase the density and reduce the moisture content, rather than oil palm trunks laminated lumber with a smaller number of layers. The increasing number of oil palm trunks layers lamination increase the value of laminated lumber mechanical properties.